Amygdala neurocircuitry at the interface between emotional regulation and narcolepsy with cataplexy - Sardar, Haniyyah; Goldstein-Piekarski, Andrea N.; Giardino, William J. (Frontiers in Neuroscience, 2023)
Narcolepsy is a sleep disorder characterized by chronic and excessive daytime sleepiness, and sudden intrusion of sleep during wakefulness that can fall into two categories: type 1 and type 2. Type 1 narcolepsy in humans is widely believed to be caused as a result of loss of neurons in the brain that contain the key arousal neuropeptide Orexin (Orx; also known as Hypocretin). Patients with type 1 narcolepsy often also present with cataplexy, the sudden paralysis of voluntary muscles which is triggered by strong emotions (e.g., laughter in humans, social play in dogs, and chocolate in rodents). The amygdala is a crucial emotion-processing center of the brain; however, little is known about the role of the amygdala in sleep/wake and narcolepsy with cataplexy. A collection of reports across human functional neuroimaging analyses and rodent behavioral paradigms points toward the amygdala as a critical node linking emotional regulation to cataplexy. Here, we review the existing evidence suggesting a functional role for the amygdala network in narcolepsy, and build upon a framework that describes relevant contributions from the central nucleus of the amygdala (CeA), basolateral amygdala (BLA), and the extended amygdala, including the bed nucleus of stria terminalis (BNST). We propose that detailed examinations of amygdala neurocircuitry controlling transitions between emotional arousal states may substantially advance progress in understanding the etiology of narcolepsy with cataplexy, leading to enhanced treatment opportunities.